Exponential stability of certain neutral differential equations - Thaned Rojsiraphisal (2018)
The neutral equation is a special case of the neutral system. In this paper we purpose new stability criteria for the neutral equation. Lyapunov functions, descriptor form and a model transformation techniques are used to guarantee exponentially stable of the neutral equation. Two examples are given to show advantage of our new criteria. © 2010 Elsevier Inc. All rights reserved.